Brand Awareness, Ethical Concerns, and Social Influence: Key Drivers of Boycotting Behavior Against Nestlé - Rosmelisa Yusof; Azura Abdullah Effendi; Nur Qistina Diyana Binti Abdul Majid; Nur Sazlein Binti Mohd Firdaus; Nur Syafiqah Binti Muhamad Shukri; Nur Syazwani Binti Mohd Hazry; Nurdania Delylah Binti Mohd Amin; Anees Janee Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Nestlé is the world’s largest food and beverage company founded in 1866 that offer a wide range of products. Nestlé present in 190 countries around the world and its headquarters in Vevey, Switzerland. In today’s global market, there has been boycott movement of Israeli products due to Israeli-Palestinian conflict. Nestlé also affected by this boycott movement since Nestlé’s products is pro-Israel products. The purpose of this study is to examine the relationship between ethical concerns, brand awareness, social influence, and consumer willingness on moral judgement and its impact on boycotting behavior against Nestlé. Data was collected from 100 respondents from various background. Our findings shows that boycotting behavior among consumer against Nestlé significantly influenced by combinations of brand awareness, ethical concerns, social influence, and consumer willingness to boycott. Meanwhile, moral judgement acts as the mediator that links all of these factors to the decision to boycott. These findings can help Nestlé to develop appropriate strategies in addressing consumer concerns and boycotting behavior against Nestlé’s products